Art and Activism: Artists amid social, environmental, and cultural crises - Suwarno (Environment-Behaviour Proceedings Journal, 2024)
Social, environmental, and cultural crises are no longer an issue but a worrying reality. In macro phenomena, it manifests as a crisis of ethics-morality, radicalism, intolerance, and rejection of diversity. This situation requires extra handling in all spaces, lines, and professions. During an extreme situation, artists and art education, along with works of art, crafts, and design, are not enough to dwell in the aesthetic, artistic, and esoteric area, let alone just for economic interests but must participate actively, concretely, build networks to carry out adaptive-innovative collaboration, to be able to be part of the solution.